Early development in Rett syndrome: the benefits and difficulties of a birth cohort approach - Marschik, Peter B.; Bölte, Sven (Developmental neurorehabilitation, 2018)
Purposes: Typically, early (pre-diagnostic) development in individuals later diagnosed with Rett syndrome (RTT) has been investigated retrospectively using parent reports, medical records and analysis of home videos. In recent years, prospective research designs have been increasingly applied to the investigation of early development in individuals with late phenotypical onset disorders, for example, autism spectrum disorder. Methods: In this study, data collected by the Danish National Birth Cohort lent itself to prospective exploration of the early development of RTT, in particular early motor-, speech-language, and socio-communicative behaviors, mood, and sleep. Results and Conclusions: Despite limitations, this quasi prospective methodology proved promising. In order to add substantially to the body of knowledge, however, specific questions relating to peculiarites in early development could usefully be added to future cohort studies. As this involves considerable work, it may be more realistic to consider a set of indicators which point to a number of developmental disorders rather than to one.